Empowering macrophages: the cancer fighters within the tumour microenvironment in mantle cell lymphoma - Nylund, Patrick; Nikkarinen, Anna; Ek, Sara; Glimelius, Ingrid (Frontiers in Immunology, 2024)
In Mantle Cell Lymphoma (MCL), the role of macrophages within the tumour microenvironment (TME) has recently gained attention due to their impact on prognosis and response to therapy. Despite their low absolute number in MCL tumour tissue, recent findings reveal an association between the levels of macrophages and prognosis, consistent with trends observed in other lymphoma subtypes. M2-like macrophages, identified by markers such as CD163, contribute to angiogenesis and suppression of the immune response. Clinical trials with MCL patients treated with chemoimmunotherapy and targeted treatments underscore the adverse impact of high levels of M2-like macrophages. Immunomodulatory drugs like lenalidomide reduce the levels of MCL-associated CD163 + macrophages and enhance macrophage phagocytic activity. Similarly, clinical approaches targeting the CD47 "don't eat me" signalling, in combination with the anti-CD20-antibody rituximab, demonstrate increased macrophage activity and phagocytosis of MCL tumour cells. Cell-based therapies such as chimeric antigen receptor (CAR) T-cell have shown promise but various challenges persist, leading to a potential interest in CAR-macrophages (CAR-M). When macrophages are recruited to the TME, they offer advantages including phagocytic function and responsiveness to microenvironment alterations, suggesting their potential as a manipulable and inducible alternative when CAR T-cell therapies fails in the complex landscape of MCL treatment.